1987
DOI: 10.1111/j.1365-2842.1987.tb00711.x
|View full text |Cite
|
Sign up to set email alerts
|

The mandibular rest position and electromyography—a review

Abstract: The objective of clinical methods for the establishment of the rest position of the mandible is to establish a position at which masticatory muscle activity is minimal. Several methods are in clinical use but these methods may not elicit a position which is coincident with the lowest level of muscle activity as determined electromyographically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

1990
1990
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 19 publications
1
6
0
1
Order By: Relevance
“…Although several studies (10,(52)(53)(54)(55)(56)(57)(58)(59)(60) found stability in the mandible at a constant position at rest and recommended the use of this position for the determination of the OVD, many other studies (32,35,(61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72)(73)(74)(75)(76) found a large variation and instability of the mandible at rest position and concluded against relying solely on physiologic rest position for the determination of the OVD. The physiologic rest position varies between individuals, from time to time in the same sitting and between sittings in the same patient, and between dental practitioners (8,32,62).…”
Section: Physiologic Rest Position and Interocclusal Distancementioning
confidence: 99%
“…Although several studies (10,(52)(53)(54)(55)(56)(57)(58)(59)(60) found stability in the mandible at a constant position at rest and recommended the use of this position for the determination of the OVD, many other studies (32,35,(61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72)(73)(74)(75)(76) found a large variation and instability of the mandible at rest position and concluded against relying solely on physiologic rest position for the determination of the OVD. The physiologic rest position varies between individuals, from time to time in the same sitting and between sittings in the same patient, and between dental practitioners (8,32,62).…”
Section: Physiologic Rest Position and Interocclusal Distancementioning
confidence: 99%
“…Postural activity -It is generally accepted that mandibular elevator muscles show a low level of activity when the mandible is in its natural position of rest (41,(67)(68)(69)(70)(71)(72). Therefore, the postural position of the mandible is controlled actively depending on head and body posifion (41,68,73,74), particularly by the active tone of temporalis muscles (68).…”
Section: Action Of Mandibular Elevator Musclesmentioning
confidence: 99%
“…Muscle relaxation is monitored by EMG recording by surface electrodes. Unfortunately, as already stated, the assumption underlying this method is mistaken, because the habitual mandibular position does not correspond to the position of minimal muscle activity (Moller, 1966;Rugh and Drago, 1981;Watkinson, 1987), and so the presumed link between these two states does not exist (see Fig. and accompanying text).…”
Section: (112) Effects Of a Modification Of Head Position On The Antmentioning
confidence: 99%